The Urgency of the Role of the Village Consultative Body (BPD) in the Formation of Participatory Village Regulations - Sugita, I Made (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2026)
To realize good governance, one of the main principles of village governance, as stipulated in Article 24 of Law Number 6 of 2014 concerning Villages, is the principle of participation, namely the involvement of the community in every government process, including the development of village regulations. The role of the Village Consultative Body (BPD), as a legislative body at the village level, is crucial as it channels community aspirations in the development of village regulations, thus resulting in participatory village regulations. The purpose of this study is to identify and analyze the urgency of the role of the Village Consultative Body (BPD) in the development of participatory village regulations. This research is normative legal research, as it examines legislation, theories or doctrines, conceptual thinking, and previous research related to the object of this study. The results indicate that the BPD's role in the development of village regulations is crucial, including serving as a means of representing and channeling community aspirations, promoting transparency and accountability in the development of village regulations, strengthening good village governance, and reducing the potential for conflict between the village government and community members during the implementation of village regulations.